Anomalous effects in the aluminum oxide sputtering yield. (22nd March 2018) - Schelfhout, R; Strijckmans, K; Depla, D
Abstract: The sputtering yield of aluminum oxide during reactive magnetron sputtering has been quantified by a new and fast method. The method is based on the meticulous determination of the reactive gas consumption during reactive DC magnetron sputtering and has been deployed to determine the sputtering yield of aluminum oxide. The accuracy of the proposed method is demonstrated by comparing its results to the common weight loss method excluding secondary effects such as redeposition. Both methods exhibit a decrease in sputtering yield with increasing discharge current. This feature of the aluminum oxide sputtering yield is described for the first time. It resembles the discrepancy between published high sputtering yield values determined by low current ion beams and the low deposition rate in the poisoned mode during reactive magnetron sputtering. Moreover, the usefulness of the new method arises from its time-resolved capabilities. The evolution of the alumina sputtering yield can now be measured up to a resolution of seconds. This reveals the complex dynamical behavior of the sputtering yield. A plausible explanation of the observed anomalies seems to originate from the balance between retention and out-diffusion of implanted gas atoms, while other possible causes are commented.